The upstairs room. - Reiss, Johanna (New York Crowell, 1972)
A Dutch Jewish girl describes the two-and-one-half years she spent in hiding in the upstairs bedroom of a farmer's house during World War II.
Continued by the author's The journey back.
Autobiographical.
Keywords: Reiss, Johanna; Reiss, Johanna; World War, 1939-1945 -- Personal narratives, Jewish -- Juvenile literature; World War, 1939-1945 -- Personal narratives, Jewish; Jews -- Netherlands; Netherlands -- History -- German occupation, 1940-1945.